2006
DOI: 10.1111/j.1440-1681.2007.04524.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bay 41‐2272 in the Pulmonary Hypertension Induced by Heparin–protamine Complex in Anaesthetized Dogs

Abstract: 1. BAY 41-2272 is a potent activator of the nitric oxide-independent site of soluble guanylate cyclase and has been recently introduced as a new therapeutic agent to treat chronic pulmonary hypertension (PH) in neonatal sheep. Because the in vivo heparin-protamine interaction may lead to severe PH, the aim of the present study was to evaluate the effects of BAY 41-2272 in the PH induced by heparin-protamine interaction in anaesthetized dogs. 2. Sixteen male dogs (10 mongrel dogs and six Beagles) were anaesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…These observations are comparable to the findings in the anesthetized dog following administration of another sGC activator, BAY 41-2272 [123]. These findings suggest that sGC activators can increase sGC enzyme activity in vascular beds from different species [123, 157]. …”
Section: Activation Of Sgc By No-like Compoundssupporting
confidence: 85%
See 1 more Smart Citation
“…These observations are comparable to the findings in the anesthetized dog following administration of another sGC activator, BAY 41-2272 [123]. These findings suggest that sGC activators can increase sGC enzyme activity in vascular beds from different species [123, 157]. …”
Section: Activation Of Sgc By No-like Compoundssupporting
confidence: 85%
“…In the intact chest rat, intravenous administration of the sGC activator, BAY 60-2770, produced dose-related decreases in systemic arterial pressure, increases in cardiac output, and decreases in systemic vascular resistance, and the cardiovascular responses were slow in onset and long in duration [157]. These observations are comparable to the findings in the anesthetized dog following administration of another sGC activator, BAY 41-2272 [123]. These findings suggest that sGC activators can increase sGC enzyme activity in vascular beds from different species [123, 157].…”
Section: Activation Of Sgc By No-like Compoundsmentioning
confidence: 80%
“…Guanylate cyclase inhibitors, such as BAY 41-2272, have been successfully used to treat animal models of cardiovascular disease, pulmonary hypertension and inflammation. [23][24][25] Alternatively, drugs that have a more cell-specific effect, such as inhibitors of phosphodiesterases (PDE) may prove more effective in specifically reversing altered SCD neutrophil function. For example, sildenafil, a PDE5-specific inhibitor, is being tested clinically in SCD patients with pulmonary hypertension 26 and should it be found that this or any other PDE is expressed in leukocytes, such PDE inhibitors may also have the potential for abrogating altered SCD neutrophil adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The pyrazolopyridine compound BAY 41-8543 is a NO-independent stimulator of sGC that has been shown to reduce systemic and pulmonary arterial pressure and relax isolated vessels from a variety of organ systems (33,37,38). BAY 41-2272 is closely related to BAY 41-8543, and this sGC stimulator has been shown to have significant pulmonary vasodilator activity in a variety of species (9,10,13,15,34,37). BAY 41-2272 has been shown to reduce right ventricular hypertrophy and pulmonary vascular remodeling in a chronic hypoxia-induced model of pulmonary hypertension (8).…”
mentioning
confidence: 99%